Actuarial analysis of the occurrence of remissions following thymectomy for myasthenia gravis in 400 patients. Issue 5 (May 1991) - Durelli, L; Maggi, G; Casadio, C; Ferri, R; Rendine, S; Bergamini, L
Abstract : The role of thymectomy in the treatment of myasthenia gravis (MG) was analysed in 400 patients affected with generalised MG operated on between 1974-83, and prospectively followed up for five years after surgery. The occurrence of stable remission (SR) (that is, complete clinical drug-free remission that remains stable for all the subsequent follow up) was the endpoint of survival analyses and the distribution of SR time (SRT, that is, the interval from thymectomy to the occurrence of SR) was assessed by actuarial and Cox multivariate analyses. SRT distribution after surgery showed a slow progressive increase of cumulative SR rate that could both be ascribed to a delayed effect of thymectomy as well as reflect the natural history of MG, itself characterised by an increasing probability of spontaneous remission with time. SRT distribution was similar after stratification for all variables studied except when patients without thymoma were stratified for the need for immunosuppressive treatment in addition to thymectomy. Patients without thymoma who did not require additional immunosuppressive therapy (n = 130) had the highest SR rate occurring in the two years after thymectomy, and differed from patients treated with immunosuppressive drugs who showed the highest SR rate five years after surgery. Actuarial analysis has therefore identified a subgroup of patients where SR, occurring in the first years after surgery, is more likely to be ascribed to thymectomy than merely reflect the natural course of the disease.